A Short Description of a Translator Writing System: (BOBS-System) - Kristensen, Bent Bruun; Madsen, Ole Lehrmann; Jensen, Bent Bæk; Eriksen, Søren Henrik (DAIMI Report Series, 1974)
This paper is itself an abstract describing a translator-writing system called the BOBS-SYSTEM, which is an implementation of some of the ideas in the Ph.D. thesis of De Remer. De Remer's thesis describes closely the parsing techniques for the hierachy of LR(K)- grammars. The main parts of the BOBS-SYSTEM are described without many details Appendix A is a short user manual for the system.